Bolnik z akutnim vnetjem mastoida s subperiostalnim abscesom ter tihim epiduralnim abscesom - Četina, Marko (Medicinski razgledi, 2005)
In this article we present a pacient who has been admited to a Department of otorinolaryngology and cervicofacial surgery at General Hospital in Celje, after external otitis with retroauricular abscess has been found in an outpatient department. It is interesting that his clinical status does not correlate with intraoperative findings and computer tomography scanning results.
Keywords: Absces; Otitis Media; Complications; Epiduralni prostor; Mastoiditis; Otitis, srednjega ušesa; Tomografija radiografska, računalniška; Tomography, X-Ray Computed; otologija; Epidural Space; Abscess; otitis; komplikacije; therapy; zdravljenje